Effect of mulching on soil moisture conservation, yield, soil properties andprofitability in apple (Malus domestica) at cold desert region inNorth-Western Himalayas - Sharma, U; Vashisth, S; Verma, S (Journal of Horticultural Sciences, 2025)
In cold desert region of lower Spiti valley in Lahaul & Spiti district of Himachal Pradesh, India, apple (Malus domestica) is grown under adverse climatic conditions like high diurnal temperature variation, negligible rainfall (
Keywords: mulching; profitability; soil moisture; soil properties; yield